An Investigation into the Rehabilitative Mechanism of Tuina in the Treatment of Sciatic Nerve Injury. (17th July 2020) - Lv, Taotao; Mo, Yanjun; Yu, Tianyuan; Zhang, Yumo; Shao, Shuai; Luo, Yuting; Shen, Yi; Lu, Mengqian; Wong, Steven Gregory
Abstract : Objective . To explore the effect of tuina on the gene expression at the point of nerve injury in rats with sciatic nerve injury (SNI) and to elucidate the repair mechanism of tuina promoting the functional recovery of peripheral nerve injury. Methods . In the Sham group, the right sciatic nerve was exposed without clamping. The SNI model was established using the sciatic nerve clamp method on the right leg and then randomly divided into the SNI group and the Tuina group. Seven days after modeling, the Tuina group was treated daily with a "massage and tuina manipulation simulator" (Patent No. ZL 2007 0187403.1), which was used daily to stimulate Yinmen (BL37), Yanglingquan (GB34), and Chengshan (BL57) with point-pressing method, plucking method, and kneading method. The stimulating force was 4N, and the stimulating frequency was 60 times per minute; each method and each point were used for 1 minute, totaling 9 minutes (1 min/acupoint/method × 3 methods × 3 acupoints). Treatment was administered for 21 days, followed by a 1-day rest after the 10th treatment, for a total of 20 times of intervention. The sciatic function index (SFI) was used to evaluate the fine movements of the hind limbs of rats in each group. The ultrastructural changes at the point of nerve injury were observed by transmission electron microscopy, and the gene changes at the point of nerve injury were detected using RNA-sequencing (RNA-seq) technology. Results . Compared with the baseline, the SFI of the SNI group and the Tuina group decreased significantly at the 0th intervention (7 days after molding); compared with the SNI group, the SFI of the Tuina group increased at the 10th intervention (P < 0.05 ) and increased significantly at the 15th and 20th intervention (P < 0.01 ). Compared with the Sham group, the myelin sheath integrity of the sciatic nerve in the SNI group was destroyed and the myelin sheath collapsed seriously, even forming myelin sheath ball, accompanied with severe axonal atrophy and mitochondrial degeneration. The tuina intervention could significantly improve the ultrastructure of the nerve injury point, and the nerve fiber myelin sheath in the Tuina group remained intact, without obvious axonal swelling or atrophy. Atrophic thread granules could be seen in the axon, but there were no vacuolated mitochondria. RNA-seq results showed that there were differences at 221 genes at the point of nerve injury between the Tuina group and the SNI group and the differentially expressed genes (DEGs) are enriched in the biological processes related to the regulation of myocyte. Regulations include the regulation of striated muscle cell differentiation, myoblast differentiation, and myotube differentiation. Conclusion . Tuina can improve the fine motor recovery and protect the myelin integrity in rats with peripheral nerve injury, and this is achieved by changing the gene sequence at the injured point.